EXAMINING NUTRITIONAL STATUS AND EMOTIONAL WELL BEING IN ADOLESCENT GIRLS THROUGH DIET QUALITY AND DEPRESSIVE SYMPTOMS: NUTRITIONAL STATUS AND EMOTIONAL FUNCTIONING IN ADOLESCENT GIRLS - S.SAI JANANI; K. LAKSHMI; G. NIRMALA DEVI; BILQUIS (The Journal of Research ANGRAU, 2026)
Adolescence is a critical developmental stage marked by heightened nutritional demandsand emotional sensitivity, particularly among girls. The present study was conducted in the year2024 with an objective to assess the diet quality and emotional functioning of 100 adolescentgirls aged 11–18 years in Guntur district of Andhra Pradesh- using the Diet Quality Index–International (DQI-I) and the Depression, Anxiety, and Stress Scale–Youth Version (DASS-Y).Dietary Information was gathered via 24-hour recall and evaluated using Indian Food CompositionTable IFCT (2017), with DQI-I scoring based on ICMR–NIN (2020) guidelines. Emotional functioningwas evaluated using DASS-Y, categorizing severity across depression, anxiety and stress. Dataon DQI-I scoring showed that 15 percent of the girls had excellent diet quality, 85 percent wereunder the “Good but Needs Improvement” category (>60–80) and none had poor diet quality(